Principles of building a new ecosystem: social, economic and legal aspects - Kaipbekova S. V., Nikiforova A. A., Iusifova Z. V., Sizova A. S., Lazarev V. A., Nikulina I. E., Shchedrina E. V., Minakov A. V., Griaznykh D. V., Kruglov V. N., Gadzaova L. P., Salavatova A. M., Feoktistova L. R., Patrusheva V. A., Artemova E. E. (Principles of building a new ecosystem: social, economic and legal aspects, 2025)
ensuring environmental safety is a priority task for all countries. Sustainable development of the state, high quality of life and health of its population can be ensured provided that high quality of the environment is maintained. In Russia, the scale of pollution by production and consumption waste has reached a critical level, posing a serious threat to national environmental security. Large industrial regions of the country face the most serious environmental problems. The purpose of the study is to study regional problems of ensuring environmental safety. In the chapteruses such research methods as analysis of theoretical sources, study of official statistics, comparative analysis. The indicators characterizing the state of the environment of the Sverdlovsk region for 2021–2023 were analyzed. It was concluded that according to the National Environmental Rating in 2023 (autumn rating), the region was in last place, i.e. it was the worst region in the country in terms of environmental indicators. Despite the improvement of certain indicators for 2021–2023 (reduction in the volume of generated waste, the share of the population in cities with high levels of air pollution, discharge of polluted wastewater, etc.), the level of pollution of the atmosphere, water resources and soils in the region is very high. Success in solving environmental problems in the region largely depends on the implementation of an integrated approach, including economic (increased investment in environmental projects), social (increased environmental literacy of the population) and technological changes (digitalization and modernization of industry).
Keywords: экология; устойчивое развитие; sustainable development; ecology; окружающая среда; environment; технологические риски; technological risks; антропологические риски; выбросы загрязняющих веществ; охраны окружающей среды; anthropological risks; pollutant emissions; environmental protection